Between training and internships: the plots of Social Work (Teresa Vigetti: Revista de Trabajo Social, 2025)
This essay seeks to recover the experience as referents of the Victim Assistance Center of the Ombudsman's Office, in the accompaniment of Social Work students. The year 2024 was marked by absurd and cruel cuts by the State, where gender and diversity policies were among the most affected. As professionals and referents of the practices, it represented an opportunity, a challenge and a way of resistance to sustain these spaces of approaches to violence, and to be able to circulate them as contents of the professional training in this problematic field.The paper seeks to account for the dynamics of training, the strategies of territorial intervention, the challenges of working with violence in disruptive contexts, such as the pandemic, and the importance of reciprocal learning between students and communities. Finally, it highlights the interdisciplinary articulation and the commitment of Social Work with the defense of human rights in complex contexts.
Keywords: Social Work; training; practices; violence; gender